Arab fire in the book "The Animal" by Al-Jahiz Its occasions, rituals and the way Al-Jahiz treated them - زردة, يوسف (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
In this research, we have shed light on one of the many aspects that Al-Jahiz mentioned in his book “The Animal” during his extensive discussion of fire in general. This aspect concerns his talk about Arab fires, in terms of the reasons for setting it, and the various occasions on which the Arabs must seek help from fire, as it is a necessity of this or that occasion. After we talked about the occasions on which fire is kindled among the Arabs, we talked about what they practice - sometimes - of behavioral, set, and verbal rituals, while they set fire on this or that occasion. After we talked about the rituals associated with setting fire, we talked about the distribution of Arab fires between the real and the figurative, or imaginary. Then we moved to talk about Al-Jahiz’s method of treating these fires, in terms of using evidence of poetry and impurity as examples, and lack of using such on evidence, other occasions, the in addition to his commenting on some of the evidence with explanations and interpretations, and not commenting on others. After that, we moved to talk about what Al-Jahiz mentioned about the aesthetics of fire, its benefits, its colors, and other different aspects of knowledge related to fire.